Answer:
(-2, 5)
Explanation:
3x + 2y = 4
4x +3y = 7
x = (2·7 -3·4)/(2·4 -3·3) = 2/-1 = -2
y = (4·4 -7·3)/-1 = -5/-1 = 5
The solution is (x, y) = (-2, 5).
_____
I used the Vedic maths variation of Cramer's Rule, because it is straightforward, and because the usual methods of elimination or substitution get messy with these coefficients.
Cramer's Rule gives you a formula for the values of x and y in the system
The formula is ...
- ∆ = ae -db
- x = (ce -fb)/∆
- y = (fa -db)/∆
The Vedic maths variation of this negates each of the terms, which has the effect of putting the products into X patterns that are relatively easy to memorize.